Application of 3D Animation Techniques Anticipation and Follow Through in Makania Season 2 Series - Kurniawan, Muhammad Abdi; Sakti, Sheanny Ocmi (Universitas Negeri Padang, 2025)
This study examines the application of the anticipation and follow through principles in 3D animation to improve motion clarity and realism. The research focuses on Makania Season 2, episode 11, titled “Next Level,” produced by Piapi Creative Media and broadcast on Astro Ceria and Sooka. The animation was developed using Blender 3.6.11 with a pose to pose workflow, including blocking, in-between, and polish stages, complemented by revisions from supervisors and clients. Motion data were obtained from real-world observation and visual references, and were applied to both human and non-human characters. Findings show that consistent use of these principles enhanced movement naturalness, emotional expression, and narrative delivery, particularly in dynamic scenes such as chases and comedic interactions. This research contributes practical insights for animators and supports the creation of visually engaging 3D animations within the Indonesian creative industry.